A hospice as an institution of palliative care functioning in health system - Wilmont, Anna (Nursing in the 21st Century, 2011)
The first hospice of St Christopher was founded in 1967 in London on a nurse - Cicely Sounders initiative. In Poland in 1981 in Cracow, Society for Ill persons started building the first stationary hospice. For the moment nowadays in our country there are over 200 hospices. They have different legal status. Among them there are stationary hospices, home-hospices, hospices for adults and for children. The main aim of these organizations is to decrease physical and mental suffering by symptom treatment - like using suitable pain-killers, professional nursing and taking care of patient and his/her family.